Students' Perceptions of the Quality of the Novel Review Text 'Laut Bercerita' Through a Digital Questionnaire - Welsi Damayanti; Halimah; Firyal Nur Wulanti (Raja Zulkarnain Education Foundation, 2026)
An example of a review of the novel Laut Bercerita (https://www.brainacademy.id/blog/con) is available on social media. This novel by Laila S. Chodiri was published in 2017 and is 394 pages thick. The structure of the novel review is: identity, orientation, synopsis, analysis, and evaluation. This study aims to describe the categories of students’ perceptions of the quality of the review text of the novel Laut Bercerita published on social media at the link https://www.brainacademy.id/blog/con. This study uses a quantitative descriptive method conducted in the odd semester of the 2025/2026 academic year in the Indonesian Language and Literature Education Study Program, Faculty of Language and Arts Education, Universitas Pendidikan Indonesia. The population of this study was third-semester students who submitted a Google Form-based questionnaire. They numbered 69 students divided into two parallel classes. This study used a total sample. Data on students’ perceptions of the quality of the review text of the novel Laut Bercerita were collected using a Google Form-based questionnaire compiled following systematic and objective procedures. A checklist was used to validate both collected and analyzed data. The research data were analyzed using descriptive statistics, namely mean and percentage, based on frequency distribution. The results showed that students' perceptions of the quality of the novel review text Laut Bercerita were categorized as high. This category indicates that there was no distortion of perception because objectively, many of the novel review texts did not meet objective aspects. However, 4 out of 10 statements were categorized as low.